Real Earnings Management, Business Strategy And Product market Competition - Braga, Luiza Dazzi (2020)
Purpose This research aims to investigate the relationships among firm-level business strategy (BS), industry-level market competition (MC), and real earnings management (REM), focusing on how BS and MC firsts jointly affect firms engagement in the man